A General Synthesis of Sphinganines through Multicomponent Catalytic Asymmetric Aziridination. Issue 7 (27th January 2014) - Mukherjee, Munmun; Zhou, Yubai; Gupta, Anil K.; Guan, Yong; Wulff, William D.
Abstract: A catalytic asymmetric synthesis of all four stereoisomers of sphinganine is described starting from hexadecanal. Utilizing either the ( R ) or ( S ) enantiomer of a BOROX catalyst, a multicomponent reaction of this aldehyde with an amine and ethyl diazoacetate gives rise to enantiomeric aziridine‐2‐carboxylates. Access to all diastereomers of sphinganine is realized upon ring opening of the enantiopure aziridine‐2‐carboxylate at the C‐3 position by direct SN 2 attack of an oxygen nucleophile, which occurs with inversion of configuration and by ring expansion of an N ‐acyl aziridine to an oxazolidinone and then hydrolysis. Overall, this process results in the formal ring opening of the aziridine with an oxygen nucleophile with retention of configuration. Abstract : The synthesis of all four stereoisomers of sphinganine was achieved by multi‐component asymmetric aziridination of hexadecanal. Complete stereocontrol is realized with the proper choice of the chirality of the BOROX catalyst and the introduction of an oxygen substituent at the 3‐position of the aziridine with either retention or inversion. MEDAM = tetramethyldianisylmethyl.